The Role of Competitive Advantage and Customer Relationship Management in Increasing Interest in Staying Back at Non-Star Hotels in Covid 19 Era - Wentri Merdiani; Umi Narimawati; Dewi Indriani Jusuf (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2021)
Indonesian nonstar hotel offers guest satisfaction, especially in terms of rooms and food. The hotel level competition is also getting higher. Guests will be more likely to choose the cheaper promotional price offered by the new hotel. However, hotels can improve the quality of their services, so prices will no longer affect guests. Hotel competitors will not always be able to provide cheap prices, because they also have to be able to cover increasingly expensive operational costs. As well as establishing business relationships with travel agents. It is recommended that employees always build a good information system and be able to solve any problems based on existing information systems. The speed of processing data in providing information and the level of ability to store data must be increased. In establishing familiarity with tourists (customer intimacy), Indonesian nonstar hotels are asked to improve the quality of service to match the expectations of tourists. In this study, we examine how CRM and competitive advantage will later increase tourist confidence in the post-Indonesian tourism destinations and industry Covid-19. Non-star hotels in the city of Bandung need reliable communication actors, both from industry the tourism sector as well as the local government that can convince and guarantee that the tourism can be relied on to improve people's welfare and increase national economy.